Cross-Sectional Study: Psychosocial Factors and Blood Pressure Abnormalities Among Students of the Faculty of Economics and Business, UPN Veteran Jakarta - Sheren Aurellia; Maria, Ima; Desi Purwaningsih; Marlina Dewiastuti (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
Background: Hypertension and prehypertension affect 10% and 14% of adolescents and young adults globally. Among university students, psychosocial stress, sleep disturbances, depression, anxiety, and caffeine consumption may synergistically trigger endothelial dysfunction and neurohumoral activation, serving as early predictors of hypertension. This study assessed the association between psychosocial factors (stress, anxiety, depression, sleep quality) and caffeine consumption with blood pressure among students of the Faculty of Economics and Business, UPN "Veteran" Jakarta, class of 2024. Method: A cross-sectional design was used, with a total population of 1,204 students, from which 66 respondents were selected via simple random sampling. Univariable and bivariable analyses were performed. Result: No significant associations were found between depression, anxiety, sleep quality, stress, caffeine intake, and blood pressure (p > 0.05), possibly due to cardiovascular homeostasis mechanisms that remain optimal in young adults, as well as chronic caffeine exposure containing bioactive compounds with antihypertensive properties that help maintain stable blood pressure. Conclusion: Depression, anxiety, stress, sleep quality, and caffeine consumption did not significantly affect blood pressure among these students. Continued monitoring of mental health and stress management by both students and institutions is recommended as part of long-term preventive strategies.